(untitled) (International relations and international law Journal, 2016)
This article discusses the main centers of power in the international community who have a huge impact on the global economy, provides economic statistics different integration structures. At the present stage regions inextricably linked political, cultural, economic and social ties and integrated into the EurAsEC may be regarded as the nucleus of a future common Eurasian space, material and geopolitical basis crystallization Eurasian megaproject.Customs Union andformed a singleeconomic space- is, inessence, isthe keytool to achievethe "Eurasianproject."Thus, thelogicalcompletion of the formationof the Eurasianintegration association- EurAsEC-ageopoliticalmegaproject-the Eurasian Union. Particular attention is paid to the project of the Eurasian Economic Union, as a new center of power in the global economy